Evidence of precursor orthorhombic domains well above the electronic nematic transition temperature in Sr(Fe1-xCox)2As2 - Kaneko, Ulisses (2019)
Raman scattering, synchrotron x-ray diffraction, specific heat, resistivity and magnetic susceptibility measurements were performed in Sr(Fe1-xCox)2As2 [x = 0.24(3)] single crystals with superconducting critical temperature Tc = 22 K and two additional transitions at 132 and 152 K observed in both specific heat and resistivity data. A quasielastic Raman signal with B2g symmetry (tetragonal cell) associated with electronic nematic fluctuations is observed. Crucially, this signal shows maximum intensity at Tnem 132 K, marking the nematic transition temperature. X-ray diffraction shows evidence of coexisting orthorhombic and tetragonal domains between Tnem and To 152 K, implying that precursor orthorhombic domains emerge over an extended temperature range above Tnem. While the height of the quasielastic Raman peak is insensitive to To, the temperature-dependence of the average nematic fluctuation rate indicates a slowing down of the nematic fluctuations inside the precursor orthorhombic domains. These results are analogous to those previously reported for the LaFeAsO parent oxypnictide [U.F. Kaneko et al., Phys. Rev. B 96, 014506 (2017)]. We propose a scenario where the precursor orthorhombic phase may be generated within the electronically disordered regime (Tnem) as long as the nematic fluctuation rate is sufficiently small in comparison to the optical phonon frequency range. In this regime, the local atomic structure responds adiabatically to the electronic nematic fluctuations, creating a net of orthorhombic clusters that, albeit dynamical for Tnem, may be sufficiently dense to sustain long-range phase coherence in a diffraction process up to To.